2011
DOI: 10.1002/cjoc.201190201
|View full text |Cite
|
Sign up to set email alerts
|

A Solution‐Phase Parallel Synthesis of 5‐Substituted 3,6‐Dihydro‐7H‐1,2,3‐triazolo[4,5‐d]pyrimidin‐7‐ones

Abstract: 5-Substituted 7H-1,2,3-triazolo [4,5-d]pyrimidin-7-ones (4) were rapidly prepared by a solution-phase parallel synthetic method, which includes aza-Wittig reaction of iminophosphorane (1) with phenyl isocynate to give carbodiimide (2) and subsequent reaction of 2 with various amine and alcohols in the presence of catalytic amount of sodium alkoxide in a parallel fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A convenient method for the synthesis of 7-aminotriazolo [4,5-b]pyridine-6-carboxylates 31 is based on the reaction of aminonitriles 29 with acetoacetic ester (30) in the presence of a Lewis acid (Scheme 7) [17].…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A convenient method for the synthesis of 7-aminotriazolo [4,5-b]pyridine-6-carboxylates 31 is based on the reaction of aminonitriles 29 with acetoacetic ester (30) in the presence of a Lewis acid (Scheme 7) [17].…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The reaction of triazolylcarbodiimides 66 with hydrazine hydrate in alcohol at room temperature also led to 5-arylamino-6-aminotriazolo[4,5d]pyrimidin-7-ones 70 (Scheme 19) [29]. To expand the boundaries of the reaction and synthesize various 5-substituted triazolo[4,5-d]pyrimidin-7-ones 72, N,N-dialkylamines, secondary amines and phenols 71 were used as nucleophilic reagents for the formation of a pyrimidine ring based on carbodiimides 66 (Scheme 20) [28,30].…”
Section: The Synthesis Of Triazolo[45-d]pyrimidines 21 Reactions Invo...mentioning
confidence: 99%
“…In addition, it can be observed that the small particles are distributed among the larger ones, that effectively uses the continuous phase (aqueous phase), which is beneficial to reduce the viscosity of the emulsion. 45…”
Section: Morphology Of Swpu-t X Dispersionsmentioning
confidence: 99%